Color planning for interiors : an integrated approach to designed spaces - Portillo, Margaret , 1962- (Hoboken, NJ : John Wiley & Sons, 2009)
One of the hallmarks of a successful designer is the ability to incorporate color into his or her projects and presentations. Beginning with a description of the multiple facets of color that accomplished designers take into consideration, this book explores color planning through the perspective of creative problem-solving
1. Color planning pathways -- 2. Art and science of color -- 3. Color perception -- 4. Color for preference -- 5. Color composition -- 6. Color for communication -- 7. Color for engagement --8. Color for pragmatics -- 9. Color criteria in concert.
Includes bibliographical references (p 203-206) and index
Keywords: Color in interior decoration